A real-world study of adverse event profiles associated with the four key components of antibody–drug conjugates based on the FAERS database - Zhang, Shuning; Ye, Chun; Zhu, Jiaxuan; Wang, Miao; Xu, Yanyan (Frontiers in Pharmacology, 2026)
BackgroundAntibody–drug conjugates (ADCs) exhibit structurally driven and highly heterogeneous toxicities, yet most pharmacovigilance studies remain drug-centered and lack systematic component-level evaluation. This study provides a comprehensive real-world safety assessment of FDA-approved ADCs using a component-based analytical framework.MethodsAll adverse event (AE) reports for 14 FDA-approved ADCs (2004–2024) were extracted from the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). ADCs and AEs were included when positive signals were simultaneously detected by four disproportionality methods (reporting odds ratio (ROR), proportional reporting ratio (PRR), information component (IC), and empirical Bayes geometric mean (EBGM)) under a multi-method consensus criterion (MCC). AEs were classified using MedDRA at the preferred term (PT) and system organ class (SOC) levels. Signal prioritization was performed by ranking ROR values within each key component type—antibody subtype, linker type, payload category, and drug-to-antibody ratio (DAR) value class, with the top 20 signals designated as “strong signals.” False discovery rate (FDR) correction was applied for sensitivity analysis.ResultsA total of 52,699 positive PT-level AE signals were included across 13 ADCs. Distinct toxicity signatures were observed across component types: IgG1-based ADCs demonstrated prominent ocular and corneal toxicity and treatment-related secondary lymphoma, whereas IgG4-based ADCs were dominated by hepatobiliary injury, vascular toxicity, bone marrow suppression, and severe infections. ADCs with cleavable linkers showed toxicity patterns enriched for treatment-related secondary lymphoma, pulmonary toxicity, and infections, while non-cleavable linker ADCs showed a highly distinctive pattern dominated by ocular toxicity, particularly corneal epithelial and stromal injury. DNA-damaging payload ADCs exhibited severe systemic toxicities, including hepatobiliary toxicity, vascular injury, interstitial lung disease, serious infections, and bone marrow suppression. In contrast, microtubule inhibitor payloads mainly produced ocular and corneal toxicity, treatment-related secondary lymphoma, and local hemorrhagic events. DAR 3–5 ADCs were highly enriched for ocular toxicity and treatment-related secondary lymphoma; DAR < 3 ADCs were characterized by hepatobiliary injury and infection-dominant patterns, and DAR > 5 ADCs demonstrated a heterogeneous multi-organ toxicity profile spanning metabolic, hepatic, pulmonary, infectious, neurological, vascular, and ocular domains. All MCC-identified PT-level AE signals remained significant after FDR correction.ConclusionThis large-scale real-world evaluation reveals clear component type-specific toxicity signatures among ADCs, supporting more targeted safety monitoring and informing rational ADC design.